Transformation of Religious Moderation through Optimization of Rohis Activities: A Systematic Analysis of Islamic Values - Ijah Bahijah; Hamidah Hamidah; M. Fachjri Kurniawan; Khalimah Tussakdiyah; Anisa Musyarrof (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to examine the transformation of Islamic Spiritual Activities (Rohis) in shaping religious moderation in the school environment. The approach used is Systematic Literature Review (SLR), by capturing data from various national scientific articles through databases such as Google Scholar and Garuda. Data collection was carried out using keywords related to "Rohis", "religious moderation", and "Islamic education" in the 2015–2024 period. Of the total 85 articles found, screening was carried out based on inclusion and exclusion criteria, and 25 articles were obtained that were further analyzed. The data analysis technique used is thematic analysis, which groups information into large patterns and themes related to Islamic values and moderation coaching strategies. The results of the study show that Rohis' activities have changed from a symbolic-ritual approach to a more contextual and responsive coaching model to the digital era. The Islamic values developed are not only normative, but also adaptive to the social dynamics of students. This study recommends the integration of digital and thematic approaches in the development of Rohis to be more effective in instilling the value of religious moderation.